2018
DOI: 10.5194/tc-12-1969-2018
|View full text |Cite
|
Sign up to set email alerts
|

Antarctic sub-shelf melt rates via PICO

Abstract: Abstract. Ocean-induced melting below ice shelves is one of the dominant drivers for mass loss from the Antarctic Ice Sheet at present. An appropriate representation of sub-shelf melt rates is therefore essential for model simulations of marine-based ice sheet evolution. Continental-scale ice sheet models often rely on simple melt-parameterizations, in particular for long-term simulations, when fully coupled ice–ocean interaction becomes computationally too expensive. Such parameterizations can account for the… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

7
218
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 133 publications
(225 citation statements)
references
References 56 publications
7
218
0
Order By: Relevance
“…We convert the CMIP5 projections of ocean temperature into a mean additional ocean sub-shelf melt forcing using the linear relationship between temperature anomaly and ice shelf melting, which is approximated for the ASE (Rignot and Jacobs, 2002), where an additional 0.1 • C temperature increase results in an increase of 1 m a −1 to the basal melt rate. The CMIP5 AOGCM forcing data that we use are relatively coarse in their spatial resolution and also do not capture sub-ice-shelf oceanographic conditions.…”
Section: Cmip5 Melt Rate Forcingmentioning
confidence: 99%
“…We convert the CMIP5 projections of ocean temperature into a mean additional ocean sub-shelf melt forcing using the linear relationship between temperature anomaly and ice shelf melting, which is approximated for the ASE (Rignot and Jacobs, 2002), where an additional 0.1 • C temperature increase results in an increase of 1 m a −1 to the basal melt rate. The CMIP5 AOGCM forcing data that we use are relatively coarse in their spatial resolution and also do not capture sub-ice-shelf oceanographic conditions.…”
Section: Cmip5 Melt Rate Forcingmentioning
confidence: 99%
“…These studies, however, are all based on ideal geometries and completely ignore basal melt under floating ice (i.e., no melt is applied under floating ice). In reality, melt can be strong, es- pecially in the vicinity of the grounding line, where it can reach ∼ 100 m yr −1 (Dutrieux et al, 2013;Rignot et al, 2013;Berger et al, 2017). Several studies have shown that, for the same melt parameterization, the choice of numerical implementation of melt has a strong impact on model results for both projections of the West Antarctic Ice Sheet Arthern and Williams, 2017) and idealized glaciers (Gladstone et al, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…Converting ocean conditions into ocean-induced melt at the base of ice shelves is an active area of research, and several parameterizations with different levels of complexity have recently been proposed for converting ocean conditions into ice 120 shelf melt rates (Lazeroms et al, 2018;Reese et al, 2018a;Pelle et al, 2019). As only a limited number of direct observations of ocean conditions (Jenkins et al, 2010;Dutrieux et al, 2014) and ice shelf melt rates Depoorter et al, 2013) exist, these parameterizations are difficult to calibrate and evaluate.…”
mentioning
confidence: 99%
“…Geothermal heat flux is from Shapiro and Ritzwoller (2004). We use the Potsdam Ice-shelf Cavity model (PICO, Reese et al, 2018a) which extends the ocean box model by Olbers and Hellmer (2010) for application in three dimensional ice-sheet models to calculate basal melt rate patterns underneath the ice shelves. We use a compilation of observed ocean temperature and salinity values 2013, Schmidtko et al, 2014) (1955, Locarnini et al, 2019 to drive PICO.…”
mentioning
confidence: 99%